Relationship between P-glycoprotein and second-generation antipsychotics. (August 2011) - Moons, Tim; de Roo, Mariska; Claes, Stephan; Dom, Geert
The membrane transport protein P-glycoprotein (P-gp) is an interesting candidate for individual differences in response to antipsychotics. To present an overview of the current knowledge of P-gp and its interaction with second-generation antipsychotics (SGAs), an internet search for all relevant English original research articles concerning P-gp and SGAs was conducted. Several SGAs are substrates for P-gp in therapeutic concentrations. These include amisulpride, aripiprazole, olanzapine, perospirone, risperidone and paliperidone. Clozapine and quetiapine are not likely to be substrates of P-gp. However, most antipsychotics act as inhibitors of P-gp, and can therefore influence plasma and brain concentrations of other substrates. No information was available for sertindole, ziprasidone or zotepine. Research in animal models demonstrated significant differences in antipsychotic brain concentration and behavior owing to both P-gp knockout and inhibition. Results in patients are less clear, as several external factors have to be accounted for. Patients with polymorphisms which decrease P-gp functionality tend to perform better in clinical settings. There is some variability in the findings concerning adverse effects, and no definitive conclusions can be drawn at this point.